The Relationship of Servant Leadership in the Classroom and Student Perceptions of University Quality of Instruction - Sparks, Betsy Harker (Archives of Business Research, 2018)
In this study, we examined students' perceptions of certain servant leader behaviors exhibited by faculty and the associated perception of effective university instruction. Five servant leadership dimensions were considered: altruistic calling, emotional healing, wisdom, persuasive mapping, and organizational stewardship. Students in the United States who were in undergraduate or graduate programs or had completed a program within the last month were invited to complete the survey instrument based on the Servant Leadership Questionnaire developed by Barbuto and Wheeler [1] and the University of Winnipeg’s Quality of University Instruction Questionnaire (UW-QUIQ) developed by Clark [4]. We used a structural equation model and found there was a positive relationship with professors exhibiting servant leadership dimensions and quality of instruction. Business professors in this study exhibited lower servant-leadership attributes in some areas and lower levels of effective university instruction than their counterparts, mandating the need for change. We suggest that these results provide insight into improving business school instruction.